Association of Serum Calcium Level with other Risk Factors of Ischaemic Stroke - A K Al Miraj; Quazi Deen Mohammad; Shahidur Rahman; Moyeenuzzaman; Shamim Miah (International Journal of Neuroinformatics, 2022)
Introduction Calcium (Ca2+) plays an important role in the pathogenesis of ischemic cell damage. Intracellular Ca2+ accumulation leads to neuronal damage by triggering the cycle of cytotoxic events, however the relationship of serum Ca levels and the pathways involved in ischemic injury is unclear. Aim of Study To investigate the relationship of serum Ca2+ levels with severity of acute ischaemic stroke, serum calcium (Ca2+) levels were measured within the first 48 hours and were compared with the clinical severity of acute ischaemic stroke. Material and Methods A hospital based cross sectional study was performed among 100 patients of acute ischaemic stroke who fulfilled the inclusion criteria. The Study was done from July 2020 to August 2021 in SPRC & Neurology Hospital Dhaka, Bangladesh And BSMMU Hospital Dhaka, Bangladesh. After hospitalization presenting complaints, physical findings of the patients were recorded. Severity of stroke was measured by NIHSS scale. Serum calcium level of every patient was measured. Calcium level was divided into 3 groups by weighted average. Statistical analysis was carried out by a non-parametric Ruska Wallis test. Results Among the 100 patients 59% were male. Among all patients 57% of patients were found to be smokers (98% male, 2% female). Among all patients 63% patients were found hypertensive and 21% of all patients (24% male, 17% female) were diabetic. Mean cholesterol level was 257.98mg/dl with standard deviation 55.49 which is above the reference range suggesting hypercholesterolemia, Triglyceride was borderline and LDL cholesterol was slightly higher and HDL cholesterol was slightly lower. Calcium level was divided into 3 groups and NIHSS score was calculated for every patient in each group. The median NIHSS score for group1 (calcium level ≤8.8 mg/dl) was 9(2-20), for group 2 (calcium level 8.9-9.6 mg/dl) was 6 (1-17) and for group 3 (calcium level ≥9.7mg/dl) was 4 (1-16). Conclusion Commonest risk factor of ischaemic stroke is hypertension. Other risk factors are smoking, diabetes mellitus and hyperlipidemia, cardiac disease. Higher serum calcium level is associated with less severity of ischaemic stroke.
Keywords: Serum Calcium Level